STUDENTS’ CHEMICAL LITERACY PROFILE ON CHEMICAL EQUILIBRIUM MATERIAL: A CASE OF CORAL REEFS TOPIC - Pratama, Faiz Ilham; Rohaeti, Eli; Laksono, Endang Widjajanti (JURNAL EDUSCIENCE, 2024)
Nowadays, chemical literacy is something important to discuss, including the benefits of chemical literacy itself. It can be the main purpose for teachers, experts, and curriculum policymakers. Chemical literacy is necessary for students since it can be a background for them to make a decision, build their critical thinking, and creativity, and help them solve daily problems or natural phenomena based on their knowledge. This research aimed to describe the students’ chemical literacy profile on chemical equilibrium materials in coral reef topics. The research question posed in this study is "What is the profile of the chemical literacy level of high school students on the topic of chemical equilibrium on coral reefs?", then this research was designed to determine the chemical literacy profile of high school students on the topic of chemical equilibrium on coral reefs. This research explains the chemical literacy profile from each aspect, chemistry in context, chemistry as knowledge, high-order learning skills, and affective aspect. The type of research is quantitative descriptive research. The research subjects were all students in grade 11th in a senior high school in Magelang who had been taught about chemical equilibrium materials. The sample of the research was 100 students in grade 11th. The research data collection technique used was a questionnaire. The instrument used was the students’ four-option close questionnaire sheet, in which the options were SD (Strongly Disagree), D (Disagree), A (Agree), and SA (Strongly Agree). Then, the data were analyzed by ideal criteria assessment. The result showed that the students’ chemical literacy profile in chemical equilibrium materials is 61.3125%. It showed that the student’s level of chemical literacy profile in chemical equilibrium materials is in a fair category. Therefore, the learning process can be modified to better support the development of high school students' chemical literacy profiles.